Rancang Bangun Sistem Pengukuran Resistivitas Geolistrik dengan menggunakan Sumber Arus Konstan: Bachtera Indarto, Gusti RE Sudenasahag, Didiek B Rahmad, M Hasan Basri, Hasto Sunarno - Bachtera Indarto, Bachtera Indarto; Gusti Rana Fahlevi Sudenasahaq, Gusti Rana Fahlevi Sudenasahaq; Didiek Basuki Rachmad, Didiek Basuki Rachmad; Muhammad Hasan Basri, Muhammad Hasan Basri; Hasto Sunarno, Hasto Sunarno (Jurnal Fisika dan Aplikasinya, 2025)
Design of geoelectric resistivity measurement system using a constant current source has been successfully created and analyzed. Geoelectric resistivity measurement system consists of a boost converter circuit, constant current source, and a microcontroller as the control system in the process of measurement and data acquisition resistivity geoelectric form of resistance data. Data acquisition system using the principles of Ohm’s law, the geoelectric method of Wenner. In this study, a constant current source that is successfully implemented on geoelectric resistivity that is a current of 0,1 mA work on resistance 0,4 until 2,345 M and a current of 1mA is working on 0,4 resistance to 8,53 k. As well as the resistance measurement can be measured by either the resistance measurement 33 to 470 k.